Software Engineering Methods in Intelligent Algorithms Proceedings of 8th Computer Science On-line Conference 2019, Vol. 1 - Silhavy, Radek; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents software engineering methods in the context of the intelligent systems. It discusses real-world problems and exploratory research describing novel approaches and applications of software engineering, software design and algorithms. The book constitutes the refereed proceedings of the Software Engineering Methods in Intelligent Algorithms Section of the 8th Computer Science On-line Conference 2019 (CSOC 2019), held on-line in April 2019. .
Literature Review on Database Design Testing Techniques -- Implication of Artificial Intelligence to Enhance the Security Aspects of Cloud Enabled Internet of Things -- S-DWF:An Integrated Schema for Secure Digital Image Watermarking -- Semantic Richness of Tag Sets: Analysis of Machine Generated and Folk Tag Set -- Analysis of behaviour patterns of the residents of a smart house -- Combined Method of Monitoring of Hazardous Phenomena and Predicting of Hazardous Processes and Security of Coastal Infrastructure and Population -- Analysis of Existing Concepts of Optimization of ETL-Processes -- Multiagent Distribution of Roles in Communities with Limited Communications -- Mac-Cormack's Scheme for Shock Filtering Equation in Image Enhancement -- Comparison Two of Different Technologies for Outdoor Positioning -- An Effective Hardware-based Bidirectional Security Aware M-Payment System by using Biometric Authentication -- A Study of DDoS reflection attack on Internet of Things in IPv4/IPv6 networks.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence